2013
DOI: 10.1590/s1677-32252013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth subsalicylate as filler particle for an experimental epoxy-based root canal sealer

Abstract: Aim: To evaluate the influence of bismuth subsalicylate addition in different concentrations on theproperties ofan experimental epoxy-based root canal sealer. Methods: Bismuth subsalicylate in 20%, 40%, 60%, 80%, 100% and 120 wt% was added tothe sealer. Flow, film thickness, working time, setting time, dimensional change, sorption, solubility and cytotoxicity were evaluated according to ISO standard. Data were statistically analyzed by one-way ANOVA and Tukey'stest with a significance level of 5% for all tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Regarding the cleaning of the prosthetic canal, studies have shown the influence of reducing remnants of obturating materials from the canal walls (18), as endodontic sealer and gutta-percha can obstruct dentinal tubules, affecting dentin permeability and reactivity, and thus impacting the adhesive interface and bond strength (19,20). Kul et al (21) observed the highest bond strength values when the prosthetic canal was irrigated with 5 mL of 5% NaOCl, followed by 5 mL of 17% EDTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the cleaning of the prosthetic canal, studies have shown the influence of reducing remnants of obturating materials from the canal walls (18), as endodontic sealer and gutta-percha can obstruct dentinal tubules, affecting dentin permeability and reactivity, and thus impacting the adhesive interface and bond strength (19,20). Kul et al (21) observed the highest bond strength values when the prosthetic canal was irrigated with 5 mL of 5% NaOCl, followed by 5 mL of 17% EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…This complex adhesive chain, where each material and substrate can be considered a link, relies on the correct bonding between them. A failure in any interface can compromise the canal's post-retention and the restoration's clinical longevity (17)(18)(19)(20)(21). In this context, cohesive failures were excluded from the bond strength calculation since they do not effectively represent the bonding strength between the materials involved in post-cementation to dentin (26).…”
Section: Discussionmentioning
confidence: 99%